(untitled) (Research, Society and Development, 2022)
Given the importance of the Integrative Project as a teaching/learning methodology for technical courses, it is necessary to frequently evaluate its results, to propose appropriate solutions for the academic requirements. Thus, the present research aimed to evaluate the Integrative Project of the subsequent technical course in agriculture and livestock with pedagogical alternation as a teaching/learning methodology capable of integrating the course curriculum with the professional experience of the labor market, with proposals for its improvement and better performance. Action-research techniques and qualitative and quantitative analyses were applied to obtain the results. The research tools used were surveys and questionnaires applied to teachers and students of the course, with the perspective of obtaining opinions about the Integrative Project of the course and verifying the achievement of its objectives. In conclusion, most teachers and students agree that the tool is insufficient to meet the goals, requiring methodological restructuring. In this way, integrating the course curriculum with the professional experience of the labor market is far from the expected, making it an uninteresting tool for the students of the technical course in agriculture and livestock.